Family history of diabetes mellitus and long-term endocrine morbidity of the offspring. (2nd October 2020) - Alon, Yuval; Wainstock, Tamar; Sheiner, Eyal; Pariente, Gali
Abstract: Background: Little is known regarding the long-term outcomes of offsprings to non-diabetic mothers with family history of diabetes mellitus (FHDM). Objective: The aim of the study was to determine whether being born to a non-diabetic mother with FHDM increases the risk for long-term endocrine morbidity. Methods: This is a population-based cohort study, comparing long-term endocrine morbidity between offspring born to non-diabetic mothers with and without FHDM. The Kaplan–Meier survival curve was used to compare cumulative morbidity incidence. Cox proportional hazards model was performed to control for confounders. Results: During the study period, 208, 728 children met the inclusion criteria. Using a Kaplan–Meier survival curve, offspring born to non-diabetic mothers with a FHDM had higher cumulative incidence of endocrine morbidity compared to their counterparts without FHDM (Log rank test p = .014). Using a Cox model, controlling for confounders, being born to a non-diabetic mother with FHDM was an independent risk factor for long-term endocrine morbidity of the offspring (adjusted HR = 1.24, 95%CI 1.001–1.54; p = .043). Conclusion: Being born to a non-diabetic mother with a FHDM is independently associated with higher risk for long-term endocrine morbidity of the offspring.